Operating in Hostile, Harsh and Remote Environment - Daniel Steffen Müller (Journal of Applied Leadership and Management, 2014)
Research questions: What are the most dangerous threats organizations are exposed to when conducting in hostile environment? What are the initial impacts and the consequential effects? What are complex incidents? Which approach to mitigate the outcome of incidents is the most effective? Is the mixture of theory and experience crucial? Is there coherence between the crisis management industry's perception and their potential costumer's expectation? Is the developed approach verified by the crisis management industry's references and academic research? What are the recommendations for the clients “risk or security buyer”. Methods: A multilateral approach, consisting of quantitative surveys and positivist qualitative interviews with experts offered the possibility to crosscheck the results of the questionnaire. Results:~ A holistic, flexible and modular crisis management approach allows companies to anticipate risks early, and mitigate them with suitable in-house solutions.
Keywords: 650